The story of the "Periodicals Button" on the Information Center web site - Gürdal, Gültekin (Information World, 2002)
This article explains the purpose the "Periodicals Button" on the web site of the Information Center at newly established university, Sabanci University was planned and launched for, and details of its infrastructure. This work also attempts to take a new perspective on the current topic of the administration of e-journals on a worldwide scale in general, and in our country, Turkey, in particular.